Implications of the breakdown in the indigenous knowledge system for rangeland management and policy: a case study from the Eastern Cape in South Africa. Issue 1 (10th February 2023) - Finca, Andiswa; Linnane, Suzanne; Slinger, Jill; Getty, David; Igshaan Samuels, M
Abstract : Communal rangelands in South Africa are generally perceived as overgrazed owing to complexities in their histories and collective utilisation which often leads to improper management. A suitable solution has not been found in land management policies because local people's contexts and their indigenous knowledge are ignored. Hence, this paper is aimed at (i) assessing the role indigenous knowledge can play in communal rangeland management, (ii) exploring working solutions to incorporate indigenous knowledge into effective communal rangeland management and land use policies, (iii) assessing mechanisms for generational transfer of indigenous knowledge. Findings from the Participatory Geographic Information System (PGIS) and Focus Group Discussion, conducted with Cata and Guquka villages in the Eastern Cape province were synthesised. This revealed that communal farmers have in-depth knowledge of their communal land, past and present rangeland management strategies and changes in rangeland condition. However, there is breakdown in the indigenous knowledge system whereby this knowledge is not being transferred and translated into good rangeland management practice, owing to the ageing population of communal farmers, limited youth involvement in livestock farming and limited access to extension services. This suggests a need for new policy approaches that would include participation of local people in policy planning and development.